Rethinking Niklas Luhmann’s theory of the phylogenesis and ontogenesis of language in light of systemic-functional linguistics - Calise, Santiago Gabriel (2015)
This paper deals with the problems of phylogenesis and ontogenesis of language, departing from Niklas Luhmann’s general hypothesis of the co-evolution of psychic and social systems. Regarding phylogenesis, the focus in Luhmann’s theory was placed on the “pre-linguistic medium of communication” constructed by gestures, which would have been the element that stimulated the evolution of language. This sort of communication allows for the emergence of a certain social order. Here, the problem was the impossibility of identifying this social order by one of the primary forms of societal differentiation. An attempt was made to interpret in which societal contexts pre-language “emerges”. In order to do this, the author resorted to Michael Halliday’s systemic-functional linguistics. Concerning ontogenesis, the attention was directed to the concepts of action and experience. The point of departure was Ilja Srubar’s criticism of Luhmann’s theory of language, according to which the acquisition of language can be thought of as a process of translating action schemes into linguistic ones. This implies a nativist vision of language discarded by Luhmann and also by Halliday. The latter indicated that it is impossible to talk about translating non-linguistic and pre-linguistic cognition schemes into linguistic form because there is no model of experience previous to the linguistic categories. In addition, an attempt was made to show that systemic-functional linguistics can be useful to fill the gap regarding the ontogenesis of language left by Luhmann’s systems theory.